Analysis of the bridge failure direction and the increased probability of collapse due to multi-hazard effects: scour and earthquakes - Bertha A. Olmos; Jose M. Jara; Alberto Gil; Juan I. López-Pérez; Guillermo Martínez; Alma R. Sánchez (Bulletin of Earthquake Engineering, 2026)

Tracking the impact of bottom trawling on benthic habitat status - Maider Plaza‐Morlote; Ana García‐Alegre; Alberto Serrano; Ulla Fernández‐Arcaya; Antonio Punzón; Ana Rodríguez‐Rúa; Sara Roman; Ana Magro; Marina Delgado; Juan Gil; José Manuel González‐Irusta (Conservation Biology, 2026)
Bottom trawling is the most widespread physical disturbance to marine benthic habitats, yet broadscale assessments of its impact remain limited. We developed a quantitative framework to evaluate trawling effects on benthic habitats at broad spatial scales based on the sentinels of seabed (SoS) indicator. We applied this approach across five broad benthic habitat types in the Bay of Biscay and the Gulf of Cádiz, two regions that are subject to substantial trawling pressure. Using data from over 2000 monitoring locations, we assessed habitat sensitivity to trawling through generalized additive models (GAMs) and the SoS indicator, which quantifies benthic habitat quality based on the proportion of sentinel species (i.e., species typical of the habitat and sensitive to the pressure). We also sought to establish scientifically grounded quality thresholds to assess bottom‐trawling impacts by applying three complementary approaches: distance to degradation, natural variation, and detectable change. We conducted a temporal analysis to evaluate changes in trawling impacts over time. Impact assessments varied depending on the method used to determine thresholds, although the natural variation and distance to degradation approaches yielded consistent results. Despite the methodological differences, all approaches identified offshore circalittoral mud and offshore circalittoral mixed sediments as the most affected habitats. The Gulf of Cádiz had more overall impacts than northern Spain. Impacts decreased significantly across all benthic habitats in association with declining trawling intensity, although extensive areas remained at risk. Our approach provides a scalable and robust way to assess seabed condition at broad spatial scales. By establishing critical benchmarks for habitat quality and pressure, it offers a scientifically sound tool to inform national and regional marine management strategies. The approach supports the implementation of environmental policies, such as the European Union Marine Strategy Framework Directive, and contributes to achieving good environmental status.

First Mediterranean Records of Two African Crabs, the Mud Crab Panopeus africanus and the Pebble Crab Ilia spinosa (Crustacea, Decapoda, Brachyura) - Alberto Gil-Fernández; Pere Abelló; Isabel Muñoz; Jose A. Cuesta (Fishes, 2026)
Two African crab species are recorded for the first time for the Mediterranean Sea. On the one hand, eight individuals of the mud crab Panopeus africanus were found in the port of Gandía, València, Spain. On the other hand, one zoea larva of the pebble crab Ilia spinosa was identified in plankton samples collected in coastal waters adjacent to L’Albufera, València, Spain. These two Mediterranean findings represent the second records for these two African crab species outside their native Atlantic distributions. Identifications were confirmed using DNA barcoding. Comparisons with other African decapod species introduced into the Mediterranean are made to assess whether they may have followed similar transport patterns, which include two main pathways, natural larval expansion from nearby Atlantic populations or accidental transport mediated by ships’ ballast water or hull fouling.

Soil carbon restoration practices offset increases in nitrous oxide emissions in the semiarid Pampa, Argentina - Frasier Ileana; Noellemeyer Elke; Posse Gabriela; Fernández Romina; Scherger Eric; Quiroga Alberto; Silvina Vargas-Gil (Soil and Tillage Research, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Exploring the interaction of high-performance triazine-based porous organic polymers with antibiotics and carbon dioxide - Pedro M.C. Matias; Sandra C.C. Nunes; João M. Gil; Maria João Ferreira; Alberto A.C. Canelas Pais; Dina Murtinho; Artur J.M. Valente (Chemical Engineering Journal, 2025)

Associations between chronic exposure to bisphenols and parabens and gut microbiota in children - Lourdes Rodrigo; Carlo Bressa; Mar Larrosa; Viviana Ramírez; Ángel Gil-Izquierdo; Cristóbal Sánchez-Muñoz; María Alba Martínez-Burgos; Alberto Zafra-Gómez; Ana Rivas (Environmental Research, 2025)

Enhancing the processability and mechanical performance of collagen-based biofilms through supercritical carbon dioxide plasticisation - Karina C. Núñez C.; Luis E. Alonso Pastor; Félix Lizalde-Arroyo; Jaime Lledó; Leandra Oliveira Salmazo; Alberto Lopez-Gil; Miguel A. Rodríguez-Pérez (Journal of Food Engineering, 2025)

Impact of changing agricultural management on the exceedance of empirical critical loads of nitrogen in terrestrial habitats of Southwestern Europe - Héctor García-Gómez; Rasmus Einarsson; Mark Theobald; Eduardo Aguilera; Tania Carrasco-Molina; Victoria Gil; Benjamín S. Gimeno; Coralina Hernández; Luis Lassaletta; Isaura Rábago; Hans J.M. van Grinsven; Marta G. Vivanco; et al. (Environmental Pollution, 2025)

Removal, bioaccumulation, and metabolization of the fluoroquinolone flumequine by Potamogeton pusillus L. - María Eugenia Valdés; Facundo Leonel Cortés; Lúcia H.M.L.M. Santos; Adrián Jaén-Gil; Sara Rodríguez-Mozaz; Daniel Alberto Wunderlin; Magdalena Victoria Monferrán (Journal of Hazardous Materials, 2025)

Biological control mitigates spread of vector-borne plant pathogens - Kris A.G. Wyckhuys; Yi Zou; David W. Crowder; Evie Adriani; Annabelle B. Albaytar; Marie Joy B. Beltran; Ibtissem Ben Fekih; Carolina Camargo-Gil; Filomena C. Sta. Cruz; Lizette Cicero; Yelitza C. Colmenarez; Claudia M. Cuellar-Palacios; et al. (Agriculture, Ecosystems & Environment, 2025)

Invasive blue vs. local Green: analysis of substrate preference of two crab species, Callinectes sapidus and Carcinus aestuarii - Filippo Piccardi; Claudio Bortot; Luca Brunoni; Federica Poli; Gil Guastoni Rosenthal; Carlotta Mazzoldi; Alberto Barausse (Marine Environmental Research, 2025)

Potential Adaptive Introgression From Dogs in Iberian Grey Wolves ( Canis lupus ) - Carlos Sarabia; Isabel Salado; Alberto Fernández‐Gil; Bridgett M. vonHoldt; Michael Hofreiter; Carles Vilà; Jennifer A. Leonard (Molecular Ecology, 2025)
Invading species along with increased anthropogenization may lead to hybridization events between wild species and closely related domesticates. As a consequence, wild species may carry introgressed alleles from domestic species, which is generally assumed to yield adverse effects in wild populations. The opposite evolutionary consequence, adaptive introgression, where introgressed genes are positively selected in the wild species, is possible but has rarely been documented. Grey wolves ( Canis lupus ) are widely distributed across the Holarctic and frequently coexist with their close relative, the domestic dog ( C. familiaris ). Despite ample opportunity, hybridization rarely occurs in most populations. Here we studied the geographically isolated grey wolves of the Iberian Peninsula, who have coexisted with a large population of loosely controlled dogs for thousands of years in a human‐modified landscape. We assessed the extent and impact of dog introgression on the current Iberian grey wolf population by analysing 150 whole genomes of Iberian and other Eurasian grey wolves as well as dogs originating from across Europe and western Siberia. We identified almost no recent introgression and a small ( DAPP1 , NSMCE4A , MPPED2 , PCDH9 , MBTPS1 , and CDH13 ) for which wild Iberian wolves carry alleles introgressed from dogs. The genes with introgressed and positively selected alleles include functions in immune response and brain functions, which may explain some of the unique behavioural phenotypes in Iberian wolves such as their reduced dispersal compared to other wolf populations.

Hunting Iberian ibex: from a threat factor to a conservation tool - Jesús M. Pérez; Fabiola Mesa-Pérez; María J. Fernández-Muñoz; José E. Granados; Paulino Fandos; Ramón C. Soriguer; Pelayo Acevedo; Pablo Refoyo; Enrique Barreñada; Juan Carlos Peral; Alberto Fernández-Arias; José A. Martínez; et al. (European Journal of Wildlife Research, 2025)
In this study we have compiled the information from official databases about Iberian ibex, Capra pyrenaica , hunting yields, hunting trophies and hunting licenses in the Spanish regions where the species is present and hunted. Such quotas showed an increasing trend between 2005–2021 and, on average, during this period, ≈ 6400 animals were yearly harvested. Despite this number decreased in 2019 and 2020 (in this last year, mainly due to the lock down caused by the COVID pandemia), the annual quota raised, reaching over 12,000 ibexes in 2021. The number of trophies increased since the 1970s and peaked in the period 2001–2005, and then declined during the period 2006–2020. At national level, the number of hunting licenses decreased from 2006 to 2021 by a 36.5%. The regional average hunting yield was significantly correlated with a regional-based ibex abundance estimation. The current situation of continued population increase together with the trophy reduction might suggest that the overall population is exceeding the carrying capacity. In this context, if hunting activity was one of the main factors involved in local extinction of the species, currently it should be considered a tool for sustainable managing of ibex populations in an scenario of increasing demographic trends and generalized absence of predators.

Effect of hydrophobic proteins in modulating the mechanical properties of lung surfactant membranes - Ainhoa Collada; Johann Mertens; Emma Batllori-Badia; Alberto Galindo; Antonio Cruz; Jesús Pérez-Gil (Chemistry and Physics of Lipids, 2025)

Highlighting the adsorption mechanism of a fluoroquinolone antibiotic from wastewater on carbon xerogel by experiments, characterization, modelling and DFT simulation - Silvia Álvarez-Torrellas; Juan Manuel Garrido-Zoido; Eduardo Alberto López-Maldonado; Ana Belén Hernández-Abreu; Vicente Ismael Águeda; José Antonio Delgado; Maria Victoria Gil; Juan García (Environmental Science and Pollution Research, 2024)

A New Coding System for the Identification of Left Ventricular Rotation Patterns and Their Relevance to Myocardial Function - Vicente Mora; Juan Geraldo; Ildefonso Roldán; Ester Galiana; Celia Gil; Pablo Escribano; Rosina Arbucci; Alberto Hidalgo; Paula Gramage; Jorge Trainini; Francesc Carreras; Jorge Lowenstein (Annals of Biomedical Engineering, 2024)
Rotational mechanics is a fundamental determinant of left ventricular ejection fraction (LVEF). The coding system currently employed in clinical practice does not distinguish between rotational patterns. We propose an alternative coding system that makes possible to identify the rotational pattern of the LV and relate it to myocardial function. Echocardiographic images were used to generate speckle tracking-derived transmural global longitudinal strain (tGLS) and rotational parameters. The existence of twist (basal and apical rotations in opposite directions) is expressed as a rotational gradient with a positive value that is the sum of the basal and apical rotation angles. Conversely, when there is rigid rotation (basal and apical rotations in the same direction) the resulting gradient is assigned a negative value that is the subtraction between the two rotation angles. The rotational patterns were evaluated in 87 healthy subjects and 248 patients with LV hypertrophy (LVH) and contrasted with their myocardial function. Our approach allowed us to distinguish between the different rotational patterns. Twist pattern was present in healthy controls and 104 patients with LVH and normal myocardial function (tGLS ≥ 17%, both). Among 144 patients with LVH and myocardial dysfunction (tGLS r = 0.73; p

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Decoding the best automated segmentation tools for vascular white matter hyperintensities in the aging brain: a clinician’s guide to precision and purpose - Lucia Torres-Simon; Alberto del Cerro-León; Miguel Yus; Ricardo Bruña; Lidia Gil-Martinez; Alberto Marcos Dolado; Fernando Maestú; Juan Arrazola-Garcia; Pablo Cuesta (GeroScience, 2024)

Correction to: Observations of golden eagles attacking and consuming wolf pups - Alberto Fernández-Gil; José M. Carral; Luis M. Barrientos; Laurentino García; Laura Benito; Miguel de Gabriel Hernando (European Journal of Wildlife Research, 2024)

Observations of golden eagles attacking and consuming wolf pups - Alberto Fernández-Gil; José M. Carral; Luis M. Barrientos; Laurentino García; Laura Benito; Miguel de Gabriel Hernando (European Journal of Wildlife Research, 2024)
Although lethal interactions between wolves and other apex carnivores have been reported for a handful of species, the killing or consumption of wolves by free-ranging golden eagles has rarely been reported. Here, we present four opportunistic field observations documenting the consumption of a wolf pup by free-ranging golden eagles and predatory behavior of eagles towards wolf pups. Although we could not confirm the killing and consumption of wolves by eagles in a single predatory event, actual predation seems plausible based on our observations. We hypothesize that these intraguild apex predators’ interactions, consisting on a smaller raptor predator attacking or consuming a lager mammal and social predator, are rare events, but provide valuable information on potential relationships across keystone apex predators.

Non-haematopoietic Sca-1+ Cells in the Retina of Adult Mice Express Functional TLR2 - Ana Flores; Laura Fernández-Sánchez; Oksana Kutsyr; Pedro Lax; Alberto Yáñez; María Luisa Gil; Daniel Gozalbo; Victoria Maneu (Stem Cell Reviews and Reports, 2024)

The dominant role of the peroxymonosulfate radical for removing contaminants in a Fenton process with metabisulfite - Giulio Farinelli; Angela Garcia Gil; Javier Marugan; Marco Minella; Debora Fabbri; Enzo Laurenti; Alberto Tiraferri; Davide Vione (Environmental Chemistry Letters, 2024)

Roots are the key for soil C restoration: A comparison of land management in the semiarid Argentinean Pampa - Ileana Frasier; Florencia Magali Barbero; Carolina Pérez-Brandan; María Florencia Gómez; Romina Fernández; Alberto Raul Quiroga; Gabriela Posse-Beaulieu; Silvina Restovich; José Meriles; Dannae Lilia Serri; Eva Lucia Margarita Figuerola; Elke Noellemeyer; et al. (Soil and Tillage Research, 2024)

Tobacco exposure, but not aging, shifts the frequency of peripheral blood B cell subpopulations - Thalyta Nery Carvalho Pinto; Cibele Cristine Berto Marques da Silva; Regina Maria Carvalho Pinto; Alberto José da Silva Duarte; Gil Benard; Juliana Ruiz Fernandes (GeroScience, 2023)

Saccharomyces cerevisiae as a biological model to study microbial responses to copper and chromium stress - María Cecilia Della Vedova; José Oscar Bonilla; María Daniela Paez; Eduardo Alberto Callegari; Raúl Andrés Gil; Liliana Beatriz Villegas (International Biodeterioration & Biodegradation, 2023)

Macrophyte complexity influences habitat choices of juvenile fish - Hilmar Hinz; Paula Anglada; Alberto Gayá Vilar; Olga Reñones; Gaetano Catanese; Julia Castro-Fernández; Maria del Mar Gil; Amalia Grau; Joan Moranta (Marine Biology, 2023)
The nursery function of littoral habitats for juvenile fish is widely recognized, but data on the specific habitat features that contribute to this function is sparse for many species, in part related to the difficulty of studying juvenile fish in their natural environment. However, this information is required to understand the potential risks of environmental change to the nursery functions of habitats. In this context, the habitat choice behaviour, with respect to differences in structural features, was evaluated for three Mediterranean littoral fish species known to be associated to macrophytes as juveniles. The overarching aim of this experiment was to determine if juveniles actively choose between different macrophyte configurations of varying complexity and height. Juveniles were exposed simultaneously to multiple visual habitat stimuli within an experimental choice arena, and their swimming behaviour was tracked by video recordings to determine the amount of time they spent near each habitat configuration. All three species showed a clear association in their occupancy towards more complex habitat configurations demonstrating that juveniles distinguished and actively selected habitats using visual cues. Subtle differences in species' affinity for complex habitats allowed us to appraise their potential vulnerabilities to habitat loss in the Mediterranean under environmental change scenarios. Furthermore, the results of this study provided evidence that differences in juvenile distribution between habitats found in previous observational studies may indeed be caused by active habitat selection, as well as through differential survivorship rates.

Burn severity and land-use legacy influence bird abundance in the Atlantic-Mediterranean biogeographic transition - Concepción García-Redondo; Paula Fernández-Moure; Miguel Cánibe; Luis Tapia; Alberto Gil-Carrera; Alba Lombao; Montserrat Díaz-Raviña; Adrián Regos (Environmental Research, 2023)

Production of Antioxidant Additives and High-quality Activated Biochar from Pyrolysis of Argan Shells - Zainab Afailal; Noemí Gil-Lalaguna; Robert J. Macías; Alberto Gonzalo; José Luis Sánchez (BioEnergy Research, 2023)
An integral valorization route based on a pyrolysis process has been proposed to find sustainable applications for argan shells focused on the simultaneous production of activated biochar and antioxidant additives from bio-oil. The bio-oil obtained in the pyrolysis process was furtherly upgraded (hydrothermal treatment and extraction process) to obtain antioxidant additives. On the other hand, the biochar obtained in the pyrolysis was used as a feedstock to produce high-quality activated biochar (by physical activation with CO 2 ). The increase in the pyrolysis temperature (350–550 °C) hardly affected the pyrolysis products distribution (biochar yields of 28–34 wt.% and bio-oil yields between 51 and 55 wt.%), but it led to a slight decrease in the content of phenolic monomers extracted from bio-oil (from 63 wt.% at 350 °C to 53 wt.% at 550 °C). When these extracted fractions were blended with biodiesel ( 2 (125 mg of CO 2 per g of the activated biochar) or phenols (complete removal of 99.6% in 4 h of contact time). It was characterized by a high BET surface area (up to 1500 m 2 /g), a high carbon content (up to 95 wt.%), low ash content (around 2 wt.%), and a pH of around 8.

Complexities underlying the breeding and deployment of Dutch elm disease resistant elms - Juan A. Martín; Jorge Domínguez; Alejandro Solla; Clive M. Brasier; Joan F. Webber; Alberto Santini; Clara Martínez-Arias; Louis Bernier; Luis Gil (New Forests, 2023)
Dutch elm disease (DED) is a vascular wilt disease caused by the pathogens Ophiostoma ulmi and Ophiostoma novo-ulmi with multiple ecological phases including pathogenic (xylem), saprotrophic (bark) and vector (beetle flight and beetle feeding wound) phases. Due to the two DED pandemics during the twentieth century the use of elms in landscape and forest restoration has declined significantly. However new initiatives for elm breeding and restoration are now underway in Europe and North America. Here we discuss complexities in the DED ‘system’ that can lead to unintended consequences during elm breeding and some of the wider options for obtaining durability or ‘field resistance’ in released material, including (1) the phenotypic plasticity of disease levels in resistant cultivars infected by O. novo-ulmi ; (2) shortcomings in test methods when selecting for resistance; (3) the implications of rapid evolutionary changes in current O. novo-ulmi populations for the choice of pathogen inoculum when screening; (4) the possibility of using active resistance to the pathogen in the beetle feeding wound, and low attractiveness of elm cultivars to feeding beetles, in addition to resistance in the xylem; (5) the risk that genes from susceptible and exotic elms be introgressed into resistant cultivars; (6) risks posed by unintentional changes in the host microbiome; and (7) the biosecurity risks posed by resistant elm deployment. In addition, attention needs to be paid to the disease pressures within which resistant elms will be released. In the future, biotechnology may further enhance our understanding of the various resistance processes in elms and our potential to deploy trees with highly durable resistance in elm restoration. Hopefully the different elm resistance processes will prove to be largely under durable, additive, multigenic control. Elm breeding programmes cannot afford to get into the host–pathogen arms races that characterise some agricultural host–pathogen systems.

Correction to: Increased Number of Passes and Double Stent Retriever Technique Induces Cumulative Injury on Arterial Wall After Mechanical Thrombectomy in a Swine Model - David Hernández; José Luis Cuevas; Laura Ludovica Gramegna; Manuel Requena; Carlos Piñana; Marta de Dios; Pilar Coscojuela; Marielle Esteves; Jiahui Li; Alberto Gil; Marc Ribó; Alejandro Tomasello (Translational Stroke Research, 2023)

Increased Number of Passes and Double Stent Retriever Technique Induces Cumulative Injury on Arterial Wall After Mechanical Thrombectomy in a Swine Model - David Hernández; José Luis Cuevas; Laura Ludovica Gramegna; Manuel Requena; Carlos Piñana; Marta de Dios; Pilar Coscojuela; Marielle Esteves; Jiahui Li; Alberto Gil; Marc Ribó; Alejandro Tomasello (Translational Stroke Research, 2023)

Contribution to low-carbon cement studies: Effects of silica fume, fly ash, sugarcane bagasse ash and acai stone ash incorporation in quaternary blended limestone-calcined clay cement concretes - Carlos Eduardo Tino Balestra; Lilyanne Rocha Garcez; Leandro Couto da Silva; Márcia Teresinha Veit; Eliziane Jubanski; Alberto Yoshihiro Nakano; Marina Helena Pietrobelli; Ricardo Schneider; Miguel Angel Ramirez Gil (Environmental Development, 2023)

Occurrence, sources, and spatial variation of POPs in a mountainous tropical drinking water supply basin by passive sampling - Daniel Gil Ramírez; Jhon Fredy Narváez Valderrama; Carlos Alberto Palacio Tobón; Juan José García; Juan David Echeverri; Jaromír Sobotka; Branislav Vrana (Environmental Pollution, 2023)

Thermochemical valorization of argan nutshells: Torrefaction and air–steam gasification - Zainab Afailal; Noemí Gil-Lalaguna; Isabel Fonts; Alberto Gonzalo; Jesús Arauzo; José Luis Sánchez (Fuel, 2023)

Parasitological and molecular identification of Trypanosoma species circulating in cattle and tsetse flies in Matutuine District, Maputo Province, Mozambique - Inocêncio Sigaúque; Paula Alberto Macucule; Fernando Chanisso Mulandane; Denise Ribeiro Arthur Brito; Suzana Augusta Jamal; Vincent Delespaux; Luís Carlos Bernardo Gil das Neves (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Ecosystem Functioning Influences Species Fitness at Upper Trophic Levels - Adrián Regos; Luis Tapia; Salvador Arenas-Castro; Alberto Gil-Carrera; Jesús Domínguez (Ecosystems, 2022)
Global change is severely affecting ecosystem functioning and biodiversity globally. Remotely sensed ecosystem functional attributes (EFAs) are integrative descriptors of the environmental change—being closely related to the processes directly affecting food chains via trophic cascades. Here we tested if EFAs can explain the species fitness at upper trophic levels. We took advantage of a long-term time series database of the reproductive success of the Golden Eagle ( Aquila chrysaetos )—an apex predator at the upper trophic level—over a 17-year period across a bioclimatic gradient (NW Spain; c. 29,575 km 2 ). We computed a comprehensive database of EFAs from three MODIS satellite-products related to the carbon cycle, heat dynamics and radiative balance. We also assessed possible time-lag in the response of the Golden Eagle to fire, a critical disruptor of the surface energy budget in our region. We explored the role of EFAs on the fitness of the Golden Eagle with logistic-exposure nest survival models. Our models showed that the reproductive performance of the Golden Eagle is influenced by spatiotemporal variations in land surface temperature, albedo and vegetation productivity (AUC values from 0.71 to 0.8; ΣWi EFAs from 0.66 to 1). Fire disturbance also affected ecological fitness of this apex predator—with a limited effect at 3 years after fire (a time-lagged response to surface energy budget disruptions; ΣWi Fire = 0.62). Our study provides evidence for the influence of the matter and energy fluxes between land surface and atmosphere on the reproductive success of species at upper trophic levels.

Host specialization is ancestral in Torymus (Hymenoptera, Chalcidoidea) cynipid gall parasitoids - Diego Gil‐Tapetado; Patricia Durán‐Montes; Mario García‐París; E. Karen López‐Estrada; Alberto Sánchez‐Vialas; Yolanda Jiménez‐Ruiz; Jose F. Gómez; Jose Luis Nieves‐Aldrey (Zoologica Scripta, 2022)
The host range of parasitoids varies greatly among species: Some only parasitize one to a few hosts (specialists), while others parasitize multiple species or a variety of host types (generalists). The direction of most host range shifts in parasitoid groups, that is from generalist to specialist or, alternatively, from specialist to generalist, is unknown. To explore the origin of host range shifts, we studied a clade within the genus Torymus (Hymenoptera, Chalcidoidea) that includes both generalist and specialist parasitoids of Cynipidae (Hymenoptera). We analysed the phylogenetic relationships of the species of Torymus on the basis of two gene fragments ( cox1 and ITS2 ) of 246 specimens and performed an ancestral state reconstruction of the specialist/generalist trait. Our results revealed the following: (a) The ancestral state of this group of Torymus is specialist, with the generalist state evolving through a loss of specialization. (b) The species Torymus cyaneus and Torymus flavipes both have a strong genetic structure, suggesting the existence of different biological identities. (c) There has been a host plant shift in the lineage(s) leading to Torymus rubi and Torymus bedeguaris from galls on Quercus to those on Rosaceae . (d) The alien species Torymus sinensis and the native European species Torymus notatus are phylogenetically closely related. (e) Speciation within Torymus was likely associated with the diversification of their cynipid hosts, which itself was driven by the dramatic changes in climate and vegetation that occurred during the Miocene.

Site-specific intra-annual rainfall patterns: a tool for agricultural planning in the Colombian sugarcane production zone - Héctor Alberto Chica Ramirez; Luis Fernando Gómez Gil; Juan José Bravo Bastidas; Javier Alí Carbonell González; Andrés Javier Peña Quiñones (Theoretical and Applied Climatology, 2021)

Population dynamics of an endangered forest bird using mark–recapture models based on DNA-tagging - María-José Bañuelos; Beatriz Blanco-Fontao; Alberto Fameli; Alberto Fernández-Gil; Patricia Mirol; María Morán-Luis; Rolando Rodríguez-Muñoz; Mario Quevedo (Conservation Genetics, 2019)

Changes in the juvenile fish assemblage of a Mediterranean shallow Posidonia oceanica seagrass nursery area after half century - CARLOS DÍAZ-GIL; AMALIA GRAU; ANTONIO MARIA GRAU; MIQUEL PALMER; REMEDIOS CABRERA; GABRIEL JORDÀ; IGNACIO ALBERTO CATALÁN (Mediterranean Marine Science, 2019)
The within-year dynamics of the juvenile fish community over a shallow nursery seagrass-dominated habitat (Posidonia oceanica) in a Mediterranean Bay was compared between two surveys separated 50 years (1960 and 2012-2013). A nocturnal survey over depths ranging from 2 to 10 m over patched seagrass meadows was conducted for one year (2012-2013) through 72 epibenthic tows spread fortnightly in 4 close-by stations, mimicking a survey, conducted in 1960, in terms of sampling intensity, sampling zone, temporal coverage and sampling gear. Although a large proportion of fish species was similar among surveys, remarkable and statistically significant differences were detected. A striking feature was that one of the most common and abundant sparidae species nowadays, Diplodus annularis, did not appear in 1960. Other strong differences included the disappearance of European eel Anguilla anguilla in the recent survey. Further, one of the most valuable species for artisanal fisheries in the area, the black scorpionfish Scorpaena porcus, was almost 10 times less abundant in 1960. A finer-scale study of the 2012-2013 survey allowed a quantitative analysis between species composition and potential environmental drivers through Redundancy Analysis that described well the current pattern of time-dependent recruitment pulses in nearshore meadows from the area through a year, with marked effects of surface temperature and photoperiod. The comparison between surveys suggests that some strong differences between surveys are unlikely attributable to interannual stochasticity in recruitment or environmental variability but may be related with i) unaccounted for habitat transformation and/or ii) the strong decrease of juvenile fishing mortality in this shallow nursery area since the enforcement of bans on littoral epibenthic trawling activities characteristic of this area.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Updating the national checklist of marine fishes in Spanish waters: An approach to priority hotspots and lessons for conservation - JOSÉ CARLOS BÁEZ; CRISTINA RODRÍGUEZ-CABELLO; RAFAEL BAÑÓN; ALBERTO BRITO; JESÚS M. FALCÓN; TOÑO MAÑO; JORGE BARO; DAVID MACÍAS; MARÍA JOSÉ MELÉNDEZ; JUAN ANTONIO CAMIÑAS; ALBERTO ARIAS-GARCÍA; JUAN GIL; et al. (Mediterranean Marine Science, 2019)
In response to a request from the Spanish Ministry of Farming, Fishing, Food, and Environment (Spanish: Agricultura, Pesca, Alimentación y Medio Ambiente) in 2015, a fish expert group was formed to provide a reference list of marine fish species according to five regions (marine demarcations) established by Spanish Law 41/2010 on the protection of the marine environment. The objective of this article was to update and analyse the data compiled in the marine fish species checklist in order to: 1) provide a complete list of marine fish species in the Spanish Exclusive Economic Zone; 2) compare this checklist between bio-geographical areas; and 3) identify possible priority hotspots for their conservation. We applied several indices, such as the total number of species in each area, species richness, and the Biodiversity Conservation Concern index. We discuss gaps in knowledge and the lessons learned for conservation purposes. A total of 1075 marine fishes were reported in Spanish waters. Most of these fish were well determined, whereas a few were treated as uncertain. The marine demarcation with the most species is the Canary Islands with 795 species, followed by the Spanish north coast demarcation with 506 species. However, the marine demarcations with the most species per area are the Spanish coast of the Gulf of Cádiz and the Strait of Gibraltar-Alboran Sea.

Lethal management may hinder population recovery in Iberian wolves - Mario Quevedo; Jorge Echegaray; Alberto Fernández-Gil; Jennifer A. Leonard; Javier Naves; Andrés Ordiz; Eloy Revilla; Carles Vilà (Biodiversity and Conservation, 2019)

Patterns of spatial distribution of Callinectes sapidus in invaded environments of the Valencian coast (Spain) - Silvia Falco; Alberto Gil-Fernández; Vicente Mocholí; Miguel Rodilla; Carmen Barberá; Alfonso Ramos-Esplá; Andrés Izquierdo (Frontiers in Marine Science, 2019)

Natural Radionuclides, Rare Earths and Heavy Metals Transferred to the Wild Vegetation Covering a Phosphogypsum Stockpile at Barreiro, Portugal - José Alberto Gil Corisco; Jan Mihalík; Maria José Madruga; Maria Isabel Prudêncio; Rosa Marques; Marta Santos; Mário Reis (Water, Air, & Soil Pollution, 2017)

Analysis of Platinum and Trace Metals in Treated Glioma Rat Cells by X-Ray Fluorescence Emission - Silvia Gil; Asunción Carmona; Gema Martínez-Criado; Alberto León; Yolanda Prezado; Manel Sabés (Biological Trace Element Research, 2015)

Glycolipid Sensing and Innate Immunity in Paracoccidioidomycosis - Vanessa G. Batista; Marcos S. Toledo; Anita H. Straus; Maria J. S. Mendes-Giannini; Alberto J. S. Duarte; Helio K. Takahashi; Gil Benard (Mycopathologia, 2014)

Exocytotic dynamics in human chromaffin cells: experiments and modeling - Almudena Albillos; Amparo Gil; Virginia González-Vélez; Alberto Pérez-Álvarez; Javier Segura; Alicia Hernández-Vivanco; José Carlos Caba-González (Journal of Computational Neuroscience, 2013)

Characterization of α/β- and γ-Gliadins in Commercial Varieties and Breeding Lines of Durum Wheat Using MALDI-TOF and A-PAGE Gels - Santiago Marín; Javier Gil-Humanes; Alberto Hernando; Francisco Barro (Biochemical Genetics, 2011)

Diet and habitat selection in Cantabrian Capercaillie (Tetrao urogallus cantabricus): ecological differentiation of a rear-edge population - Beatriz Blanco-Fontao; Alberto Fernández-Gil; José Ramón Obeso; Mario Quevedo (Journal of Ornithology, 2010)

Light response in seedlings of a temperate (Quercus petraea) and a sub-Mediterranean species (Quercus pyrenaica): contrasting ecological strategies as potential keys to regeneration performance in mixed marginal populations - Jesús Rodríguez-Calcerrada; Jose Alberto Pardos; Luis Gil; Peter B. Reich; Ismael Aranda (Plant Ecology, 2008)

Subspecies Cantabrian capercaillie Tetrao urogallus cantabricus endangered according to IUCN criteria - Ilse Storch; María José Bañuelos; Alberto Fernández-Gil; José Ramón Obeso; Mario Quevedo; Rolando Rodríguez-Muñoz (Journal of Ornithology, 2006)

Screening European Elms for Resistance to Ophiostoma novo-ulmi - Alejandro Solla; Jürgen Bohnens; Eric Collin; Stephanos Diamandis; Albrecht Franke; Luis Gil; Margarita Burón; Alberto Santini; Lorenzo Mittempergher; Jean Pinon; An Vanden Broeck (Forest Science, 2005)
Resistance breeding of the native elms against Dutch elm disease, caused by the fungus Ophiostoma novo-ulmi Brasier, is a major objective in Europe for the conservation of this tree species. More than 2,500 cuttings of 324 elm clones (Ulmus minor Miller, U. glabra Huds., U. laevis Pall., U. pumila L., U. minor x U. glabra, and U. minor x U. pumila) from eight European countries, planted in several randomized two-block designed plots were inoculated with various O. novo-ulmi strains. Crown wilting and dieback were recorded during the first year after inoculation. The wilting of the control trees varied among the plots, making the results difficult to compare, but analysis of variance (ANOVA) within each plot showed significant differences in disease severity among the clones tested, allowing study of the variation of the response among elm taxa. Results showed that 19 European inoculated clones recovered from O. novo-ulmi attack, giving hope for the reestablishment of native elms in countryside hedges and forests. FOR. SCI. 51(2):134–141.

Shoot growth components and flowering phenology in grafted Pinus halepensis Mill. - Marta Pardos; Jos Climent; Luis Gil; Jos Alberto Pardos (Trees, 2003)

Field study of beech (t Fagus sylvatica L.) and melojo oak (t Quercus pyrenaica Willd) leaf litter decomposition in the centre of the Iberian Peninsula - Fernando Pardo; Luis Gil; Jose Alberto Pardos (Plant and Soil, 1997)